Problematika Koneksi Matematis Berbasis Nilai-nilai Islam Siswa MTs Pada Materi Bilangan Bulat - Litsa Arfi Hidayati; Kusno (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
Difficulties in connecting mathematics to everyday life based on Islamic values remain a challenge for students at Madrasah Tsanawiyah (MTs). This study aims to analyze the obstacles students face in applying mathematical concepts within an Islamic context at MTs MINAT Cilacap. This research employs a qualitative descriptive method with three seventh-grade students selected through purposive sampling as subjects. Data collection was carried out through open-ended tests, semi-structured interviews, and observations, which were then analyzed using triangulation techniques. The results of the study indicate that high-achieving students can integrate mathematical concepts with Islamic principles when solving problems. However, some students struggle to connect problems, understand mathematical concepts, and relate them to Islamic teachings and real-life situations. The factors influencing these differences include understanding fundamental concepts, analytical thinking skills, and the ability to identify the relevance between mathematics and Islamic values.